Overlapping Central-Regional Authorities in the Unitary State of the Republic of Indonesia: Problems of Decentralization Design and Governance Reconstruction - Muh Farhan Arfandy; Amin Nugrah Santoso; Aryoko Abdurrachman; Shofiyatu Jahra (Activa Yuris: Jurnal Hukum, 2026)
The dynamics of central-regional relations in Indonesia's post-Reform constitutional system continue to fluctuate, particularly with the advent of the Omnibus Law regime (Job Creation Law), which has fundamentally altered the landscape of decentralization. This article examines the structural problems of overlapping authority, which are no longer merely administrative but have created a regulatory vacuum and legal uncertainty at the local level. Using normative legal research methods with statutory and conceptual approaches, this study analyzes the disharmony between the Regional Government Law as the basis of autonomy and various sectoral laws that tend to be centralistic. The findings indicate that centralization of licensing without adequate central supervisory capacity has weakened environmental control functions and hindered public service effectiveness. As a solution, this article proposes a reconstruction of the authority distribution model through five strategic pillars: (1) regulatory harmonization placing the Regional Government Law as the lex generalis; (2) revitalization of the subsidiarity principle returning execution functions to the regions; (3) institutionalization of non-litigation administrative dispute resolution mechanisms; (4) a shift towards outcome-based accountability; and (5) the implementation of asymmetric decentralization and multi-level governance. This reconstruction aims to build a synergistic, accountable, and responsive central-regional relationship within the framework of the Unitary State of the Republic of Indonesia.